Faktor-Faktor yang Mempengaruhi Ketepatan Waktu Pelaporan Keuangan pada Perusahaan di Bursa Efek Indonesia - Theodora Florence Tomasoa; Kevin Hermanto Tupamahu (Universitas Pattimura, 2025)
Timeliness in financial reporting is a crucial indicator of transparency and accountability in capital markets. This study examines the effects of profitability, audit quality, and firm size on the timeliness of financial reporting among manufacturing companies listed on the Indonesia Stock Exchange during 2010–2013. A quantitative approach with an explanatory design was employed, involving 89 companies (356 observations) selected through purposive sampling. Data were analyzed using binary logistic regression. The results show that all three independent variables significantly influence reporting timeliness when tested simultaneously. Partially, only profitability and audit quality have significant effects, while firm size does not. The adjusted R² value of 0.037 indicates that the model explains only 3.7% of the variability in reporting timeliness. These findings emphasize the importance of profitability and audit quality, although their contributions are limited. Practically, companies should enhance financial performance and engage high-quality auditors to improve the timeliness of financial reporting